2005
DOI: 10.1590/s0004-27302005000100019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, endocrine and metabolic features in Turner syndrome

Abstract: Turner syndrome is one of the more common genetic disorders, associated with abnormalities of the X chromosome, and occurring in about 50 per 100,000 liveborn girls. Turner syndrome is usually associated with reduced adult height, gonadal dysgenesis, and thus insufficient circulating levels of female sex steroids, and infertility. A number of other signs and symptoms are seen more frequent with the syndrome. Morbidity and mortality is increased. The average intellectual performance is within the normal range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 67 publications
7
117
0
8
Order By: Relevance
“…Ohne entsprechende medizinische Hilfe zur Reproduktion bleiben derzeit etwa 95% aller erwachsenen Frauen mit Ullrich-Turner-Syndrom kinderlos [10,15,27]. Neuere Untersuchungen zeigten jedoch, dass bei betroffenen Adoleszenten in Gewebeproben des Ovars Primärfolli-kel gefunden werden [16].…”
Section: Fertilität Beim Ullrich-turner-syndromunclassified
“…Ohne entsprechende medizinische Hilfe zur Reproduktion bleiben derzeit etwa 95% aller erwachsenen Frauen mit Ullrich-Turner-Syndrom kinderlos [10,15,27]. Neuere Untersuchungen zeigten jedoch, dass bei betroffenen Adoleszenten in Gewebeproben des Ovars Primärfolli-kel gefunden werden [16].…”
Section: Fertilität Beim Ullrich-turner-syndromunclassified
“…The incidence of short stature in girls with a confirmed diagnosis of Turner syndrome ranges between 80% and 98% and is more common in patients with a complete deletion of one of the X chromosomes [1][2][3][4]. The average adult height achieved is around 20 cm shorter than the normal female population [1][2][3][4]. Previous studies investigating the GH axis in girls with Turner syndrome demonstrated normal growth hormone levels [5][6][7][8] or low levels in response to GHRH stimuli, mainly in 45,X girls [9].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of short stature in girls with a confirmed diagnosis of Turner syndrome ranges between 80% and 98% and is more common in patients with a complete deletion of one of the X chromosomes [1][2][3][4]. The average adult height achieved is around 20 cm shorter than the normal female population [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Turner syndrome (TS) occurs in about 50 per 100,000 girls and is defined by a partially or completely absent X chromosome (4). The majority of patients with TS have a 45,X karyotype; in addition, short-or long-arm deletion, ring X, isochromosome, and mosaicism have been reported.…”
mentioning
confidence: 99%
“…The majority of patients with TS have a 45,X karyotype; in addition, short-or long-arm deletion, ring X, isochromosome, and mosaicism have been reported. The cardinal features include growth retardation with reduced adult height with or without additional features like minor facial dysmorphism, associated anomalies, gonadal insufficiency, and infertility (4). Coarctation of the aorta is the commonest congenital heart disease both in KS and in TS.…”
mentioning
confidence: 99%